Fabrication and Characterization of Ibuprofen and Ceftriaxone loaded Electrospun Cellulose Acetate Nanofiber Layers as a Model of Targeted Drug Delivery System - Novrynda Eko Satriawan; Junaidi Khotib; Muhamad Nasir; A. H. Zaidan (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2022)
This study aims to study the process of fabricating and characterization nanofibers based on cellulose acetate polymer filled with ceftriaxone and ibuprofen using the electrospinning method as a model for a targeted drug delivery system. Cellulose acetate has been successfully fabricated into nanofibers using the electrospinning method and filled with ceftriaxone and ibuprofen. The resulting nanofibers have an average diameter in the range of 412.5 – 558.5 nm under the conditions of the electrospinning process, namely 22 kV voltage, 15 cm distance, and flow rate. 0.005 mL/min using acetone/DMAc (2:1). Based on the data generated from the FTIR test, homogeneity, and drug release test, it is known that the resulting nanofibers, namely cellulose acetate, cellulose acetate-ceftriaxone, and cellulose acetate-ibuprofen, have good morphological characteristics, homogeneity, and release rate so that they have the potential to be used as a targeted drug delivery system